Everyday world-making : toward an understanding of affect and mothering - Lane, Julia; Joensuu, Eleonora (Demeter Press, 2018)
This cross-disciplinary collection considers the intersection of affect and mothering, with the aim of expanding both the experiential and theoretical frameworks that guide our understanding of mothering and of theories of affect. It brings together creative, reflective, poetic, and theoretical pieces to question, challenge, and re-conceptualize mothering through the lens of affect, and affect through the lens of mothering. The collection also aims to explore less examined mothering experiences such as failure, disgust, and ambivalence in order to challenge normative paradigms and narratives s.